PsycEXTRA Dataset 2014
DOI: 10.1037/e574242014-089
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol Intoxication and Cognitive Emotion Regulation Strategies on Lab-Based Partner Aggression

Abstract: Intimate partner aggression (IPA) is a serious national health concern that affects an alarming number of individuals and can lead to substantial psychological and physical suffering. Situational risk factors that arise in the immediate context of IPA reflect statelike influences that trigger aggression. Because these factors are more variable and fluctuate according to the situation, they are potentially promising targets for prevention and intervention efforts (e.g., through cognitive and behavioral interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 198 publications
(280 reference statements)
0
2
0
Order By: Relevance
“…While inconsistent with the other aggression paradigms discussed in this section, the Proximal Antecedents to Violent Episodes Scale (PAVE; Babcock et al, 2004) is a 20-item self-report measure that assesses IPA propensity using Likert-type responses with higher scores representing a greater likelihood of aggressing across situations (e.g., my partner interrupts me while I’m talking). Watkins (2014) experimentally manipulated alcohol consumption in order to assess the impact on IPA propensity, measured using a modified version of the PAVE in which participants were instructed to respond as if each situation were in real time. Results indicated that individuals in the alcohol condition displayed greater IPA propensity as measured by the provocative items on the PAVE Scale compared to individuals in the placebo condition (Watkins, 2014).…”
Section: Online Compatible Aggression Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…While inconsistent with the other aggression paradigms discussed in this section, the Proximal Antecedents to Violent Episodes Scale (PAVE; Babcock et al, 2004) is a 20-item self-report measure that assesses IPA propensity using Likert-type responses with higher scores representing a greater likelihood of aggressing across situations (e.g., my partner interrupts me while I’m talking). Watkins (2014) experimentally manipulated alcohol consumption in order to assess the impact on IPA propensity, measured using a modified version of the PAVE in which participants were instructed to respond as if each situation were in real time. Results indicated that individuals in the alcohol condition displayed greater IPA propensity as measured by the provocative items on the PAVE Scale compared to individuals in the placebo condition (Watkins, 2014).…”
Section: Online Compatible Aggression Paradigmsmentioning
confidence: 99%
“…Watkins (2014) experimentally manipulated alcohol consumption in order to assess the impact on IPA propensity, measured using a modified version of the PAVE in which participants were instructed to respond as if each situation were in real time. Results indicated that individuals in the alcohol condition displayed greater IPA propensity as measured by the provocative items on the PAVE Scale compared to individuals in the placebo condition (Watkins, 2014). The use of an electronic PAVE Scale is well suited to pairing with anger provocation for online assessment, particularly to the extent that responses to the PAVE are subject to situational factors.…”
Section: Online Compatible Aggression Paradigmsmentioning
confidence: 99%